True life adventures Volume 21975-1976 Lands of exploration - Disney, Roy Edward; Disney, Walt, $d 1901-1966; Buena Vista Home Entertainment (Firm); Walt Disney Home Entertainment (Firm) (Burbank, CA Walt Disney Home Entertainment Distributed by Buena Vista Home Entertainment, 2006)
The Living Desert is a study of plant and animal life in the arid plain which stretches from Oregon to Mexico and from California to Texas. Includes scenes of a death struggle between a hawk and a rattlesnake, an encounter between a bobcat and wild pigs, a contest between two male turtles for the favor of a female, and the courtship dance of a pair of scorpions. Also shows a time-lapse sequence of desert flowers coming into bloom. The Vanishing Prairie presents information about the area between the Mississippi River and the Rocky Mountains. In addiition to exploration of animal life, historical concepts about American Indians and early pioneer settlements are included. Seal Island presents the spring return of the animal inhabitants to the Pribilof Islands of Alaska. Mainly focuses on the fur-bearing seals, including formation of harems and the raising of pups
DVD release of episodes of the Disney television program True life adventurers originally broadcast 1975-1976
1
Keywords: Animal behavior; Desert animals; Nature; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs